2016
DOI: 10.1246/cl.151031
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity and Selectivities of Metal Oxides and Pt/Al2O3 for NH3 Combustion

Abstract: Catalytic activity and selectivities of metal oxides and Pt/Al 2 O 3 were evaluated for the combustion of NH 3 , which is considered a carbon-free energy source. Catalytic NH 3 combustion using 3d transition metal oxides for the stoichiometric NH 3 O 2 reaction showed the following order of activity: MnO 2 > Co 3 O 4 > CuO > Fe 2 O 3 μ V 2 O 5 > NiO. This order implies that the activity increases with decreasing oxygen bond energy of the metal oxides. CuO exhibited higher N 2 selectivity than the other transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…[10][11][12][13] Fewstudies have been devoted to stoichiometric mixtures. [3,14,15] Thus,there is aneed to develop new ammonia combustion systems.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13] Fewstudies have been devoted to stoichiometric mixtures. [3,14,15] Thus,there is aneed to develop new ammonia combustion systems.…”
mentioning
confidence: 99%
“…[15] The combustion reaction is also easier to sustain for catalytic reaction. [15] The combustion reaction is also easier to sustain for catalytic reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we proposed novel catalytic NH 3 combustion systems that enable low ignition temperatures as well as negligible N 2 O/NO x emissions, 14)16) and reported that the NH 3 combustion activity of metal oxides increases with a decrease in their metaloxygen bond energy. 14) In addition, a novel catalyst, copper oxide (CuO x ) supported on aluminum oxide borates (10Al 2 O 3 ·2B 2 O 3 : 10A2B) with high performance for NH 3 combustion, was successfully prepared. 15) Although CuO x -based catalysts have also been widely studied for the selective oxidation of NH 3 emissions to reduce air pollution, 17), 18) there are no published studies of the catalytic local structures during NH 3 combustion and/or the oxidation reaction over the well-known supported CuO x .…”
mentioning
confidence: 99%
“…The main body of research into ammonia oxidation is devoted to the ammonia slip reaction from diesel engines where the reaction is operated in an excess of oxygen . Few studies have been devoted to stoichiometric mixtures . Thus, there is a need to develop new ammonia combustion systems.…”
Section: Figurementioning
confidence: 99%